Metabolic Profiling and Gene Expression Analyses of Purple-Leaf Formation in Tea Cultivars (Camellia sinensis var. sinensis and var. assamica) - Zhu, Ming-zhi; Zhou, Fang; Ran, Li-sha; Li, Yi-long; Tan, Bin; Wang, Kun-bo; Huang, Jian-an; Liu, Zhong-hua (Frontiers in Plant Science, 2021)
Purple-leaf tea cultivars are known for their specific chemical composition that greatly influences tea bioactivity and plant resistance. Some studies have tried to reveal the purple-leaf formation mechanism of tea by comparing the purple new leaves and green older leaves in the same purple-leaf tea cultivar. It has been reported that almost all structural genes involved in anthocyanin/flavonoid biosynthesis were down-regulated in purple-leaf tea cultivars when the purple new leaves become green older leaves. However, anthocyanin/flavonoid biosynthesis is also affected by the growth period of tea leaves, gradually decreasing as new tea leaves become old tea leaves. This leads to uncertainty as to whether the purple-leaf formation is attributed to the high expression of structural genes in anthocyanin/flavonoid biosynthesis. To better understand the mechanisms underlying purple-leaf formation, we analyzed the biosynthesis of three pigments (chlorophylls, carotenoids, and anthocyanins/flavonoids) by integrated metabolic and gene expression analyses in four purple-leaf tea cultivars including Camellia sinensis var. sinensis and var. assamica. Green-leaf and yellow-leaf cultivars were employed for comparison. The purple-leaf phenotype was mainly attributed to high anthocyanins and low chlorophylls. The purple-leaf phenotype led to other flavonoid changes including lowered monomeric catechin derivatives and elevated polymerized catechin derivatives. Gene expression analysis revealed that 4-coumarate: CoA ligase (4CL), anthocyanidin synthase (ANS), and UDP-glucose: flavonoid 3-O-glucosyltransferase (UFGT) genes in the anthocyanin biosynthetic pathway and the uroporphyrinogen decarboxylase (HEME) gene in the chlorophyll biosynthetic pathway were responsible for high anthocyanin and low chlorophyll, respectively. These findings provide insights into the mechanism of purple-leaf formation in tea cultivars.